1998
DOI: 10.1086/515355
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofLeishmaniaDNA by Polymerase Chain Reaction in Scars of Treated Human Patients

Abstract: Leishmaniasis is an endemic disease in developing countries. The efficacy of therapy is usually evaluated through clinical parameters. To define the parasitologic cure, 20 patients were biopsied before and 1 month to 8 years after treatment. Paraffin-embedded tissue was used for DNA isolation. All patients had a positive polymerase chain reaction (PCR) result before therapy, except 1, for whom no histopathologic material was available. The causative agent was identified as belonging to the Leishmania (Viannia)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
98
1
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 8 publications
3
98
1
10
Order By: Relevance
“…Quanto à discordância entre a negatividade da pesquisa de amastigotas em relação à positividade das culturas, sem dúvida a leitura das culturas é mais fácil porque requer menor habilidade técnica. Também, a cultura de leishmânia tem mais alto percentual de positividade que a pesquisa de amastigotas em esfregaço, e o achado de DNA de leishmânia, em cicatrizes de pacientes tratados com antimonial, é referido na literatura 17 .…”
unclassified
“…Quanto à discordância entre a negatividade da pesquisa de amastigotas em relação à positividade das culturas, sem dúvida a leitura das culturas é mais fácil porque requer menor habilidade técnica. Também, a cultura de leishmânia tem mais alto percentual de positividade que a pesquisa de amastigotas em esfregaço, e o achado de DNA de leishmânia, em cicatrizes de pacientes tratados com antimonial, é referido na literatura 17 .…”
unclassified
“…Some studies have shown that the persistence of Leishmania DNA in blood or bone marrow of treated visceral leishmaniasis patients is associated with disease relapse or the appearance of post-kala azar dermal leishmaniasis (Osman et al 1997). Furthermore, PCR permitted the detection of Leishmania (Viannia) DNA in scars of clinically cured cutaneous leishmaniasis patients, demonstrating the persistence of the parasite (Schubach et al, 1998). Likewise, the scar of one of these patients was also positive by culture (Schubach et al 1998).…”
mentioning
confidence: 99%
“…A positive control, consisting of 100 pg DNA extracted from an axenic culture of Leishmania braziliensis, was also performed. The DNA from the agarose gels was transferred to nylon membranes by capillary blotting using 0.4 N NaOH and hybridized against Leishmania (Viannia)-specific probes as described elsewhere (Schubach et al 1998, Pirmez et al 1999). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because L. panamensis and L. braziliensis are the most prevalent species among human cases innovación y dEsarrollo dE productos XV Congreso Colombiano de Parasitología y Medicina Tropical of cutaneous leishmaniasis and infection is not eliminated by treatment (Schubach, et al, 1998;Vergel, et al, 2006), decades of monotherapeutic use of antimonial drugs is likely to have selected tolerant and even resistant populations of these species that could have been disseminated in circumstances of anthroponotic transmission.…”
Section: Discussionmentioning
confidence: 99%